Nephrotic syndrome sera induce different transcriptomes in podocytes based on the steroid response - Martin Bezdicka; Ondrej Cinek; Valerij Semjonov; Katerina Polackova; Eva Sladkova; Jakub Zieg; Moin A. Saleem; Ondrej Soucek (Physiological Reports, 2024)
Abstract As the molecular mechanism of nephrotic syndrome remains largely undiscovered, patients continue to be exposed to the pros and cons of uniform glucocorticoid treatment. We explored whether the exposure of in vitro‐cultivated podocytes to sera from children with steroid‐sensitive or steroid‐resistant nephrotic syndrome induces differences in gene expression profiles, which could help to elucidate the pathogenesis of the steroid response. Human immortalized podocytes were cultivated with patient sera for 3 days. After cell lysis, RNA extraction, 3′‐mRNA libraries were prepared and sequenced. There were 34 significantly upregulated and 14 downregulated genes (fold difference <0.5 and >2.0, respectively, and false discovery rate‐corrected p < 0.05) and 22 significantly upregulated and 6 downregulated pathways (false discovery rate‐corrected p < 0.01) in the steroid‐sensitive (n = 9) versus steroid‐resistant group (n = 4). The observed pathways included upregulated redox reactions, DNA repair, mitosis, protein translation and downregulated cholesterol biosynthesis. Sera from children with nephrotic syndrome induce disease subtype‐specific transcriptome changes in human podocytes in vitro. However, further exploration of a larger cohort is needed to verify whether clinically distinct types of nephrotic syndrome or disease activity may be differentiated by specific transcriptomic profiles and whether this information may help to elucidate the pathogenesis of the steroid response.